Les effets conjoints du travail et des horaires alternants sur la santé des agents de surveillance des établissements pénitentiaires - Pierre Pavageau (Perspectives Interdisciplinaires sur le Travail et la Santé)
The aim of our study is to compare the effects of three different forms of time organization (traditional 9 to 5 schedule, 6-hour shifts, and 12-hour shifts) inside French prisons, and particularly on prison guard staff. Complementary means of investigation (questionnaire, work observations, statistical treatment) were used to attempt to evaluate the difference between the effect of working hours and of the actual work on the guards’ health. Staff who worked 12-hour shifts had more positive results than staff who worked 6-hour shifts. This was mainly due to the advantages in their private lives. At the same time, some signs of fatigue prevent us from conclusively favouring this type of working rhythm. Beyond the alternation of schedules, the actual work content also has an important impact on the workers’ health.